Autologous stem cell transplantation for primary mediastinal B-cell lymphoma: long-term outcome and role of post-transplant radiotherapy : a report of the European Society for Blood and Marrow Transplantation - Avivi, Irit; Boumendil, Ariane; Finel, Hervé; Nagler, Arnon; de Sousa, Aïda Botelho; Santasusana, Josep Maria Ribera; Vandenberghe, Elizabeth; Afanasyev, Boris; Bordessoule, Dominique; Moraleda, José Maria; Garcia, Eulogio Conde; Pohlreich, David; et al. (Bone marrow transplantation, 2018)
The purpose of this retrospective registry study was to investigate the outcome of autoSCT for primary mediastinal B-cell lymphoma (PMBCL) in the rituximab era, including the effects of eventual post-transplant radiotherapy (RT) consolidation. Patients with PMBCL aged between 18 and 70 years who were treated with a first autoSCT between 2000 and 2012 and registered with the EBMT were eligible. Eighty-six patients with confirmed PMBCL and the full data set required for this analysis were evaluable. Sixteen patients underwent autoSCT in remission after first-line therapy (CR/PR1), 44 patients were transplanted with chemosensitive relapsed or primary refractory disease (CR/PR >1), and 24 patients were chemorefractory at the time of autoSCT. With a median follow-up of 5 years, 3-year estimates of relapse incidence, progression-free survival, and overall survival were 6%, 94%, and 100% for CR/PR1; 31%, 64%, and 85% for CR/PR >1; and 52%, 39%, and 41% for REF, respectively. Whilst there was no significant benefit of post-transplant RT in the CR/PR >1 group, RT could completely prevent disease recurrence post d100 in the refractory group. In conclusion, autoSCT with or without consolidating RT is associated with excellent outcome in chemoimmunotherapy-sensitive PMBCL, whereas its benefits seem to be limited in chemoimmunotherapy-refractory disease.